The role and challenges of cluster randomised trials for global health. Issue 5 (May 2021) - Dron, Louis; Taljaard, Monica; Cheung, Yin Bun; Grais, Rebecca; Ford, Nathan; Thorlund, Kristian; Jahan, Fyezah; Nakimuli-Mpungu, Etheldreda; Xavier, Denis; Bhutta, Zulfiqar A; Park, Jay J H; Mills, Edward J
Abstract : Summary: Evaluating whether an intervention works when trialled in groups of individuals can pose complex challenges for clinical research. Cluster randomised controlled trials involve the random allocation of groups or clusters of individuals to receive an intervention, and they are commonly used in global health research. In this paper, we describe the potential reasons for the increasing popularity of cluster trials in low-income and middle-income countries. We also draw on key areas of global health research for an assessment of common trial planning practices, and we address their methodological shortcomings and pitfalls. Lastly, we discuss alternative approaches for population-level intervention trials that could be useful for research undertaken in low-income and middle-income countries for situations in which the use of cluster randomisation might not be appropriate.